DEALING WITH DYSFUNCTION IN THE NATION'S INCREASINGLY OBSOLETE SYSTEM FOR LAND USE MANAGEMENT: Guidance From The Past for State-Coordinated Planning and Decision-Making. - Fobi, Lum. (2017)
Abstract: Urban sprawl, socioeconomic segregation, ecological neglect, environmental injustice, and unequal allocation of public services - these all illustrate some of the unfortunate consequences of America's unguided and uncoordinated land use system. Since the initial adoption of the current system for land use planning and control, massive industrialization, population growth, urbanization, and technological advancement, have occurred across the nation. However, our land use system remains unreformed and thus incapable of addressing the immediate and future obstacles that arise in an ever evolving nation. This analysis of land use governance in the United States examines the dysfunctions and impacts of the nation's locally-dominated land use system, and explores how an historical attempt to enact national land use policy legislation could offer a pragmatic solution to improve the planning and control of our human and land resources in the challenging years to come. Part I analyzes the development and function of the current U.S. land use system. Part II analyzes the dysfunctions of uncoordinated and unguided land use decision-making. Finally, Part III explores how a modified version of the national land use legislation proposed by Senator Henry M. Jackson over 40 years ago could beneficially reform the current dysfunctional land use system in order to achieve far better management of the nation's land resources.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Jonathan Witten.; Committee: Zygmunt Plater.; Keywords: Land use planning, and Law.